Substance, rights, value, and abortion - Simkulet, William (Bioethics, 2019)
Most serious contemporary opposition to abortion is grounded on the belief that human fetuses are members of the same moral category as beings like us, and that the loss of any such life is one of the worst possible losses. Substance view theorists oppose abortion for this reason: in their view beings like us are essentially rational substances with inherent moral worth, and those who perform induced abortion fail to recognize this moral worth. In a recent series of articles, Rob Lovering presents reductio-style arguments against the substance view, in part arguing that it is inconsistent with our intuitions in rescue and spontaneous abortion cases. In a recent reply, Henrik Friberg-Fernros argues that the substance view can evade these problematic implications because of a distinction between killing and letting die. According to this argument, the fetus’s right to life is a negative right not to be killed, not a positive right to be rescued, thus the anti-abortion theorist who lets fetuses die acts acceptably. I argue this stance fails to recognize the inherent moral worth that the substance view contends fetuses possess. One who refrains from saving a person, or doesn’t care how many people she saves, cannot reasonably claim to value life. Furthermore, this stance is at odds with most contemporary anti-abortion views that oppose induced abortions of both the killing and letting die variety.